APPROACHES TO EVALUATION OF EFFICIENCY OF FINANCIAL SUPPORT OF INNOVATIVE DEVELOPMENT OF AGRICULTURAL SECTOR OF THE REGION - Sus, T.Y. (The actual problems of regional economy development, 2022)
Modern approaches to assessing the effectiveness of financing innovative development are considered. It is noted that in modern world practice there is a use of a wide range of indicators that assess the level of innovation development and the impact of various factors. Modern innovation policy and its financing is formed which is related to natural and climatic conditions, terrain and specialization of agricultural production. A compromise approach to the differentiation of innovation and financial policy by goals and instruments, based on the specifics of each region, has been proposed for the agricultural sector of Ukraine. This approach to financial support for innovative development of the agricultural sector leads to the transition from centralized distribution of financial resources to decentralization and the development of competitive forms of support from both the government and local governments. It is noted that in modern conditions the problems of assessing the innovation potential of the region are considered by Ukrainian and foreign scientists who use different approaches. The most used approaches to assessing the innovation potential of the region are resource, structural, process and integrated. Criteria for assessing the effectiveness of financing the innovative development of the agricultural sector of the region are outlined. The main methods are identified, each of which uses certain approaches to the formation of the structure of factors and evaluation methods. The purpose of the study is to outline approaches to assessing the effectiveness of financial support for innovative development of the agricultural sector. The novelty of the study is the formation of an algorithm for assessing the effectiveness of financial support for innovative development of the agricultural sector, which is based on the regional specifics of the agricultural sector. The research methodology is based on the comparative method and the method of analysis and synthesis when considering approaches to assessing the effectiveness of financial support for innovative development of the agricultural sector of the region.